Limiting Central Bank Credit to the Government : Theory and Practice - Cottarelli, Carlo (Occasional Papers; Occasional Paper ;, 1993)
This paper examines central bank independence with reference to the constraints on central bank credit to the government, focusing on how such credit should be regulated. It discusses why credit should be contsrained, and in which forms, and how to implement those constraints.